Mengapa Minat Belajar Matematika Siswa Rendah? Kajian Eksploratif mengenai Hambatan Internal dan Eksternal pada Siswa Madrasah Tsanawiyah - Musdalipa Juanda; Nursupiamin; Yulia (Mandalika Mathematics and Educations Journal, 2026)
This descriptive qualitative study at MTs Nida’ul Khairaat Pombewe explores the internal and external barriers affecting the mathematics learning interest of Grade VIII students. Data were gathered through questionnaires, observations, interviews, and documentation, then analyzed using the Miles and Huberman model.The results reveal that internal barriers include negative attitudes, low self-confidence, and cognitive difficulties. Meanwhile, external barriers encompass monotonous teaching methods, one-way interaction, and a lack of family support and conducive classroom environments. These factors interact to worsen low student interest. In conclusion, low learning interest is a multidimensional phenomenon requiring interactive, student-centered pedagogical strategies to create a more supportive learning environment.